Pengaruh Total Asset Turnover (TATO) dan Debt to Equity Ratio (DER) Terhadap Return On Equity (ROE) Pada PT. Barito Pacific Tbk. Periode 2013 – 2023 - Modefa Levie; Nur Mukholipah; Triyadi Triyadi (Jurnal Ekonomi dan Bisnis Digital, 2025)
The purpose of this study is to determine the effect of Total Asset Turnover (TATO) and Debt to Equity Ratio (DER) on Return On Equity (ROE) at PT Barito Pacific Tbk for the period 2013–2023, both partially and simultaneously. The method used is a quantitative approach. The sample consists of the financial statements of PT Barito Pacific Tbk over 11 years. The sampling technique used is Non-Probability Sampling. The analysis in this study was conducted using the SPSS (Statistical Package for Social Science) software version 29.0. The results of the study show that Total Asset Turnover (TATO) does not have a significant effect on Return On Equity (ROE), based on the t-test (Partial Test), with a significance value of 0.859 (> 0.05). Debt to Equity Ratio (DER) also does not have a significant effect on Return On Equity (ROE), based on the t-test (Partial Test), with a significance value of 0.792 (> 0.05). Total Asset Turnover (TATO) and Debt to Equity Ratio (DER) do not simultaneously affect Return On Equity (ROE), based on the F-test (Simultaneous Test), which shows a significance value of 0.946 (> 0.05). This indicates that there is no significant simultaneous effect of Total Asset Turnover (TATO) and Debt to Equity Ratio (DER) on Return On Equity (ROE).